Lexical Modality in Presidential Election Discourse in Selected Nigerian Online Newspapers (2011 – 2019) - Adebiyi, Oluwabusayo (Journal of Language and Literature Studies, 2025)
Public opinion columns in the Nigerian online newspapers often provide vital information on sociopolitical issues. Previous studies on political media discourse focused on how public opinions shape pre-election political debates and speeches in Nigeria. However, little attention was paid to how linguistic choices constrain public opinions, especially on Nigerian presidential election results. This study is designed to investigate the representation of public opinions on the Nigerian presidential election results in Nigerian online newspapers, with a view to determining the public opinion types and linguistic forms. This study adopts Norman Fairclough’s Dialectical-relational model to Critical Discourse Analysis, complemented by M. A. K. Halliday’s Systemic Functional Grammar as the framework. These approaches provide a method for studying language use in the discourses of Nigerians on the Nigerian presidential election results. The descriptive design was adopted. Six popular Nigerian online newspapers (Vanguard, Punch, Nigerian Tribune, The Nation, Leadership, and The Guardian) published between February and April of the election years in 2011-2019 were purposively selected because of their robust contents  on Nigerian presidential election results, are critically examined and subjected to linguistic and qualitative method of analysis. Data are purposively selected from editorials, open letters, and comments based on election  and attitudes of people to the presidential election results in Nigeria. The analysis revealed the lexical modality is used by people to express their views  towards the  presidential election results in  Nigeria.